Epidemiology and molecular characterisation of multidrug-resistant Escherichia coli isolated from chicken meat. - Hamida Khanom; Chandan Nath; Philip P Mshelbwala; Md Ridoan Pasha; Ricardo Soares Magalhaes; John I Alawneh; Mohammad Mahmudul Hassan (PLoS ONE)
Ensuring the safety of poultry products is critical for public health, particularly due to the rising concern of antimicrobial resistance (AMR) in foodborne pathogens. This study aimed to investigate the prevalence and antimicrobial resistance (AMR) patterns of Escherichia coli (E. coli) isolated from broiler chicken meat samples collected from live bird markets (LBMs) and supermarkets (SMs) in the Chattogram Metropolitan Area (CMA), Bangladesh. A total of 430 samples, comprising 215 liver and 215 muscle samples, were collected between October 2020 and February 2021 from nine LBMs and five SMs. Samples were processed and cultured, and E. coli was isolated and identified through phenotypic and molecular techniques, including PCR targeting the uidA and uspA genes. Antimicrobial susceptibility testing (AST) was conducted using the Kirby-Bauer disk diffusion techniques with seven antibiotics from six distinct antimicrobial classes. The study found an overall prevalence of 56.28% (95% CI: 51.56-60.89) for E. coli. The prevalence in LBMs (58.33%) was higher than in SMs (54.80%), with liver samples showing a slightly higher rate of contamination (63.33% in LBMs, 55.20% in SMs) compared to muscle samples. AMR profiling revealed high resistance rates to sulfamethoxazole-trimethoprim (88.84%), tetracycline (86.78%), and ampicillin (82.23%). Conversely, cephalexin (63.64%) and gentamicin (57.02%) had the highest susceptibility rates. A significant proportion (84.71%) of isolates were multidrug-resistant (MDR), with some isolates resistant to up to six classes of antimicrobial. The multiple antibiotic resistance (MAR) index ranged from 0.14 to 1.00, indicating substantial antimicrobial exposure. PCR analysis confirmed the presence of the blaTEM gene in all ampicillin-resistant isolates, while 75.35% of sulfamethoxazole-resistant isolates carried the sul2 gene. Correlation analysis revealed a strong association between phenotypic resistance to ampicillin and the presence of the blaTEM gene (r = 1), along with a moderate correlation between sul2 and resistance to sulfamethoxazole (r = 0.5). These findings highlight the widespread presence of multidrug-resistant (MDR) E. coli in broiler meat, posing a significant public health concern.